Pandemic preparedness and response in service hub cities: lessons from Northwestern Ontario. Issue 3 (3rd September 2021) - Schiff, Rebecca; Krysowaty, Bonnie; Hay, Travis; Wilkinson, Ashley
Abstract : Purpose: Responding to the needs of homeless and marginally housed persons has been a major component of the Canadian federal and provincial responses to the COVID-19 pandemic. However, smaller, less-resourced cities and rural regions have been left competing for limited resources (Schiff et al., 2020 ). The purpose of this paper is to use a case study to examine and highlight information about the capacities and needs of service hub cities during pandemics. Design/methodology/approach: The authors draw on the experience of Thunder Bay – a small city in Northern Ontario, Canada which experienced a serious outbreak of COVID-19 amongst homeless persons and shelter staff in the community. The authors catalogued the series of events leading to this outbreak through information tracked by two of the authors who hold key funding and planning positions within the Thunder Bay homeless sector. Findings: Several lessons may be useful for other cities nationally and internationally of similar size, geography and socio-economic position. The authors suggest a need for increased supports to the homeless sector in small service–hub cities (and particularly those with large Indigenous populations) to aid in the creation of pandemic plans and more broadly to ending chronic homelessness in those regions. Originality/value: Small hub cities such as Thunder Bay serve vast rural areas and may have high rates of homelessness. This case study points to some important factors for consideration related to pandemic planning in these contexts.